Pierścień Kołowy dla Pewnego Szczególnego Przypadku Obciążenia - Czudek, H. (Engineering Transactions, 1962)
This paper gives a solution of the problem of a circular ring under a vertical load uniformly distributed along the horizontal projection and a side load by horizontal pressure of trapezoidal distribution.The type of the loads assumed corresponds approximately to the assumption that the tube is composed of short segment and buried in earth.The solution is obtained by means of the Muskhelishvili method by expanding the load along the outer contour in a complex Fourier series. The function φ (z) and ψ (z) are sought in the form of a Laurent's series.